Synthesis of nanocages for application as nano-size reactors/containers - Song, Lixin (2008)
Self-assembly of block copolymers (BCPs) have recently received much attention because of its ability to form microdomains that are tens of nanometers. Modified block copolymer has proved to be a promising way of preparing nanoparticles, as the chemistry of the various blocks can be made use to form domains of a variety of shape and size. In this study block copolymer polystyrene-b-poly(4-vinylpyridine) (PS-P4VP) were synthesized by anionic polymerization and characterized using DSC, FTIR, NMR, SEC. Its self-assembled morphology was investigated using TEM and AFM. We have for the first time synthesized polystyrene-b-poly(4-vinylpyridine) (PS-P4VP) betaine copolymers using PS-P4VP copolymer as a precursor. Solution properties studies and morphology investigations confirmed that the sultone-induced micellization led to the formation of ribbon shape nanostructures. It was also found that a core-corona inversion can be induced in-situ with water for PS-P4VP-sultone. The morphology of the micellar film can be tuned from hexagonal array of dots to ribbon-like by annealing or solvent treatment. Both annealing and solvent treatment add a facile yet effective tool for controlling pattern formation. Gold nanoparticles, titania nanoparticles and Au-Ag alloy nanoparticles were synthesized in PS-P4VP micelle or PS-P4VP-sultone micelle by in-situ reduction. This procedure gives rise to monodisperse nanoparticles. The use of gold-polymer film as a memory device is also illustrated.